THE RELEVANCE OF WAQF TO THE AUSTRALIAN SOCIETY FROM THE PERSPECTIVE OF MAQASID AL-SHARI’AH (HIGHER OBJECTIVES OF SHARI’AH) - Gebara, Rawaa El Ayoubi (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2018)
Philanthropic institutions (awqāf) were very functional vis-à-vis socio-religious aspects and the public welfare system in the early days of Islam. Gradually, however, the development of waqf (pl. awqāf) degenerated and is now limited to Muslim-majority countries and specifically consists of the religious kind. Nonetheless, can Muslims and non-Muslims benefit from waqf in a majority non-Muslim country like Australia? The primary objective of this paper is to study the relevance of waqf to the Australian secularised society from the perspective of maqāṣid al-Sharīʿah. Therefore, I will examine how maqāṣid al-Sharīʿah is achieved in the introduction of waqf in Australian society, and how waqf can be rejuvenated to serve the purpose of maqāṣid al-Sharīʿah, which aims to preserve life, intellect, religion, progeny and property. The methodology used in this paper is analytical and critical. The primary sources of Islamic knowledge, such as Qurʾan and sunnah, will be studied carefully. Secondary sources will also be studied and analysed critically to explore the findings. The worth of this paper lies in drawing the attention of stakeholders like policy makers, lawyers, leaders and the general public to the contemporary relevance and need for awqāf in achieving social justice for the ongoing benefit of the general public. This paper is a humble effort in evaluating the possibility of the application of waqf in Australia and to justify how far this product achieves maqāṣid al-Sharīʿah. A comprehensive and careful examination of the methodology of maqāṣid al-Sharīʿah entails an understanding that Sharīʿah aims to protect and preserve public interest (maṣlaḥa) in all aspects of life.